Aktualisasi Nilai-nilai Pancasila dalam Upaya Membangun Karakter Anak-anak di ”Pesantren Pondok Quran Boarding School” Kecamatan Cilengkrang Kabupaten Bandung - Nataniela, Shira Putri; Kamil, Najwa Naila Rahma; Ramadhan, Muhammad Syafiq; Raikhansyah, Arrafi; Ginanjar, Agi; Febriyani, Rizka Aulia; Syaqieb, Albar; Alhakim, Agisna Malik; Agustiyani, Riva Esya; Herdiana, Dian; Pahman, Ilham (Nanggroe: Jurnal Pengabdian Cendikia, 2026)
Pancasila is the fundamental ideology of the Indonesian state and should serve as a guiding principle in national and civic life; however, the implementation of its values within society remains limited. In the educational context, Islamic boarding schools pondok pesantren play a crucial role in character formation based on Pancasila values, particularly the Second Principle, “Just and Civilized Humanity,” which aligns with the pesantren’s mission to develop generations with akhlaqul karimah (noble character). These values are believed to be implemented through moral development and residential routines at Pondok Quran Boarding School. Therefore, this study aims to analyze and describe specifically how the values of the Second Principle of Pancasila are actualized in efforts to build students’ character at Pondok Quran Boarding School. This study employs a Participatory Action Research (PAR) approach with a qualitative design that emphasizes active involvement and collaboration between the researchers (university students) and participants (students). The actualization of Pancasila values, particularly the Second Principle, was carried out through socialization activities and a series of stages, including planning, preliminary observation, implementation of educational activities in the field, and reflection. The findings indicate that the PAR approach through interactive educational programs is effective as a medium for the actualization and internalization of the Second Principle of Pancasila among junior high school students. These activities make a tangible contribution to strengthening students’ character by fostering respect for human dignity, building civilized relationships, and creating a culture of mutual respect and a healthy learning environment within the school.